PERAN PEREMPUAN DALAM TRANSFORMASI KEUANGAN RUMAH TANGGA: PENERAPAN APLIKASI KEUANGAN DIGITAL UNTUK MERENCANAKAN ANGGARAN DAN MENGELOLA UTANG DENGAN EFISIEN - Sutanto, Hermawan; Victor; Gurusinga, Latersia Br; Yusnaini (AKUNTANSI DEWANTARA, 2025)
The transformation of finance in Indonesia is entering the digital era, marked by an increase in financial inclusion, rapid growth of financial technology companies, and the expanding use of e-wallets and digital payments. Women play an important role in this process, not only as users but also as participants and leaders, supporting sustainable economic growth. Although data shows that women still face a digital divide, government efforts through the Ministry of Communication and Information Technology focus on empowering women to access and utilize digital technology. In the context of households, homemakers play a key role in financial management, including budgeting and debt management. This research employs a mixed methods approach to analyze the use of digital financial applications by 80 homemakers in Medan Johor District. The results indicate that, despite a high level of digital application usage, challenges such as limited knowledge and training hinder the effectiveness of these applications in financial management. It was also found that applications are more frequently used for transactions rather than for financial planning. Therefore, comprehensive training programs are needed to enhance financial literacy and empower women to optimally utilize technology, which in turn can improve household financial well-being.